RELATIONSHIP BETWEEN COMPUTER SELF-EFFICACY AND RESEARCH ATTITUDE: A QUANTITATIVE STUDY OF TERTIARY INSTITUTIONS IN ENUGU STATE, NIGERIA - Nwakwoala, Joshua N. Nwakwoala (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
The present study investigated the relationship between computer self-efficacy and research attitudes in academia. One hundred and six academic staff conveniently pooled from tertiary institutions completed a self-report questionnaire intended to evaluate their ability to use the computer and its impact on their research-related attitudes. A cross-sectional design was employed in the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, Version 23). Linear regression was run to test the hypothesis that computer self-efficacy would interact with research attitudes. The investigation revealed that computer self-efficacy statistically significantly predicted research attitudes in academia at F (1,104), 47.35, P<.000. An observation of the R2 indicates that the predictor variable accounted for 11.7% of the observed variance in research attitudes. The result has implications for research development in tertiary institutions